4-Aminopyridine as a Single Agent Diagnostic and Treatment for Severe Nerve Crush Injury. (21st March 2019) - Noble, Mark; Tseng, Kuang-Ching (Chris); Li, Haiyan; Elfar, John C
Abstract: Background: Traumatic peripheral nerve injury (TPI) is a major medical problem without effective treatment options. There is no way to diagnose or treat an incomplete injury and delays contribute to morbidity. We examined 4-aminopyridine (4-AP), a potassium-channel blocker as a possible treatment for TPI. Methods: We used standard mouse models of TPI with functional outcomes including sciatic-functional-index, sensory indices, and electrodiagnostics; in addition to standard immunohistochemical, and electron microscopic correlates of axon and myelin morphology. Results: Sustained early 4-AP administration increased the speed and extent of behavioral recovery too rapidly to be explained by axonal regeneration. 4-AP also enhanced recovery of nerve conduction velocity, promoted remyelination, and increased axonal area post-injury. 4-AP treatment also enabled the rapid distinction between incomplete and complete nerve lesions. Conclusion: 4-AP singularly provides both a new potential therapy to promote durable recovery and remyelination in acute peripheral nerve injury and a means of identifying lesions in which this therapy would be most likely to be of value. The ability to distinguish injuries that may respond to extended therapy without intervention can offer benefit to wounded soldiers.